Kafka in Action - Scott, Dylan (Manning Publications Co. LLC, 2022)
Kafka in Action introduces the core features of Kafka, along with relevant examples of how to use it in real applications. In it, you'll explore the most common use cases such as logging and managing streaming data. When you're done, you'll be ready to handle both basic developer- and admin-based tasks in a Kafka-focused team.